DETEKSI BIAS GENDER PADA INSTRUMEN EVALUASI BELAJAR KIMIA DENGAN METODE MANTEL-HAENZEL - Rizki Nor Amelia; Sri Rejeki Dwi Astuti; Anggi Ristiyana Puspita Sari (UIN Sumatera Utara Medan, 2022)
This study aims to explore psychometric characteristics and detect whether the teacher-made chemistry learning evaluation instrument contains item bias that can benefit students of a certain gender. The research sample was 358 students of class XII SMA in Yogyakarta who were taken by cluster random sampling then the answer were analyzed by Winsteps Rasch Software 3.73. In general, it can be concluded that the teacher-made chemistry learning achievement instrument is good in terms of the reliability coefficient, the distribution of the difficulty level of the items, the majority of which are in the medium category, and only one that detected as misfit item. The results of the analysis using the Mantel-Haenszel method showed that three item was biased and two of them favored male students. With the detection of bias item, it indicates that follow-up from the teacher is needed to improve these items so that the principle of test fairness can be enforced.